The Specifics of Learning Dialog Skills by Preschoolers with Autism Spectrum Disorders - Adilzhanova, M.A.; Tishina, L.A. (Autizm i narušenie razvitiâ, 2024)
Objectives. The variability of disorders in the formation of dialog skills of preschoolers with autism spectrum disorders (ASD) does not always depend on the level of intellectual development. In issues of speech development, it is important to take into account both the specifics of understanding the reversed speech at the level of interrogative statements, and the aspects of structuring and semantics of the answer proposed by the child with ASD himself. In order to study the specifics of mastering the basic conversational skills by children with ASD who have unimpaired intellect, a special pilot study was designed and conducted. Methods. The peculiarities of understanding questions of various purposes and structures by students of the age of 5-7 years (group 1 - 51 children) with unimpaired intellect and ability of verbal communication were studied. Children of group 1 and preschoolers of group 2 of younger age (from 3 years 10 months to 5 years 2 months, a total of 28 participants) were presented with 48 questions, hierarchically organized based on ontogenetic patterns associated with the formation of cognitive concepts, which are accessible to a typically developing child by a certain age. The results obtained in both groups were compared. Results. Only 2.3% of the proposed 3,708 questions remained unanswered, and the number of correct (adequate) answers, depending on age, tended to increase (for example, preschoolers with ASD of 4 years gave 68% correct answers, preschoolers of 5 years - 73%). The study shows that, in terms of nature and specifics of dialog skills, students with ASD 5-7 years old have no significant differences from the typically developing preschoolers of a younger age group: the number and quality of correct answers from children with ASD at the age of 6 years is comparable with the number of correct answers from typically developing preschoolers of 4 years old. Conclusions. In the process of forming dialog skills in the structure of developmental education for children with ASD, the teacher should rely solely on the traditional spontaneous question-and-answer method, they should also consider the semantics and pragmatics of the proposed lexical material. The data obtained will be useful for special education teachers in selecting the content for speech development, taking into account the individual typological characteristics of children with ASD. Актуальность и цель. Вариативность нарушений при формировании диалоговых навыков у дошкольников с расстройствами аутистического спектра (РАС) не всегда зависит от уровня интеллектуального развития. В вопросах развития речи важно учитывать не только специфику понимания обращенной речи на уровне вопросительных высказываний, но и аспекты структурирования и семантики ответа, предложенного самим ребенком с РАС. С целью изучения специфики усвоения базовых диалоговых навыков детьми с РАС, имеющими сохранный интеллект, спроектировано и проведено специальное пилотное исследование. Методы и методики. Изучались особенности понимания вопросов разного назначения и структуры обучающимися с РАС 5-7-ми лет (группа 1 - 51 ребенок), имеющими сохранный интеллект и владеющими вербальной коммуникацией. Детям группы 1 и дошкольникам группы 2 более младшего возраста (от 3-х лет 10-ти месяцев до 5-ти лет 2-х месяцев, всего 28 участников) предлагались 48 вопросов, иерархия которых строилась с учетом онтогенетических закономерностей, связанных с формированием когнитивных концептов, доступных нормативно развивающемуся ребенку к определенному возрасту. Полученные в обеих группах результаты сопоставлялись. Результаты. Из предложенных 3708 вопросов только 2,3% остались без ответа, а число правильных (адекватных) ответов в зависимости от возраста имело тенденцию к увеличению (например, у дошкольников с РАС 4-х лет - 68%, 5-ти лет - 73%). В ходе исследования показано, что по характеру и специфике диалоговых навыков обучающиеся с РАС 5-7-ми лет не имеют существенных отличий от нормативно развивающихся дошкольников более младшей возрастной группы: количество и качество правильных ответов детей с РАС в возрасте 6-ти лет практически сопоставимо с количеством правильных ответов нормативно развивающихся дошкольников 4-летнего возраста. Выводы. В процессе формирования диалоговых навыков в структуре коррекционно-развивающего обучения детей с РАС педагог не должен ограничиваться традиционной спонтанной вопросно-ответной формой работы, ему следует также опираться на семантику и прагматику предлагаемого лексического материала. Полученные данные будут полезны педагогам коррекционного профиля при отборе содержания коррекционно-педагогической работы по развитию речи с учетом индивидуально-типологических особенностей детей с РАС.